Alterations of Gut Microbiome in Patients with Colorectal Advanced Adenoma by Metagenomic Analyses - Jingyuan Xiang; Ningli Chai; Longsong Li; Xinwei Hao; Enqiang Linghu (The Turkish Journal of Gastroenterology)
Background/Aims: Colorectal cancer (CRC) is one of the deadliest cancers worldwide, mostly arising from adenomatous polyps. Mounting evidence has demonstrated that changes in the gut microbiome play key roles in CRC progression, while quite few studies focused on the altered microbiota architecture of advanced adenoma (AA), a crucial precancerous stage of CRC. Thus, we aimed to investigate the microbial profiles of AA patients.